Characterization of tropical granite properties based on the degree of weathering / Ahmad Syauqi Md Hasan and Nur Masyitah Osman - Md Hasan, Ahmad Syauqi; Osman, Nur Masyitah (2012)
Weathering process weakens the cementation and bonding conditions between particles and changes the properties of rock such as strength, p-wave velocity, porosity and electrical conductivity. All of these properties are representative physical, engineering and dynamic properties which show the particle formation changes due to the weathering process. Thus, the study on the characterization of tropical granite properties wascarried outtaking into consideration the degree of weathering. Granitic rock samples were prepared according to the various degrees of weathering. Micro level porosity was estimated by using the analytical image processing technique from the images which were taken from the electro microscope. Amacro level porosity was also determined by the saturation and caliper techniques with the same specimen. Uniaxial compressive strength tests were conducted in order to determine the strength of the intact rock specimen. Meanwhile, p-wave velocity and electrical conductivity test was conducted to measure the p-wave velocity and the resistance ability of rock specimens. In conclusion, as the degree of weathering increases the porosity of the granite increases, p-wave velocity decreases, resistivity decreases. It was found that strength of granite decreases as the weathering degree increases since contact forces acting on the particle skeleton increases as the porosity increases.